Perinatal morbidity and mortality in preeclampsia - Alcántara Ascón, René (2015)
A prospective study was conducted May to November 1988 in the Archbishop Loayza Hospital in Lima, in order to determine whether there is a significant statistical association of perinatal morbidity and mortality between mild and severe preeclampsia. Normal, mild and severe toxemic: 300 cases divided equally into 3 groups were evaluated. Age and parity was similar in the groups studied. Before 37 weeks born 2% and 20% of fetuses of pregnant women with mild and severe disease respectively. 94% and 100% of patients with mild and severe toxemia is not controlled respectively. Born by caesarean 28% in mild cases and 56% for severe. Fetal weights kept inversely related to the severity of the disease. Perinatal morbidity was observed in 8% and 45% of mild and severe respectively (p <0.001) cases, with the most common causes fetal dystrophy, asphyxia, and prematurity. They died perinatally 1% and 7% of the products of pregnant women with mild and severe disease respectively (p <0.05), and were due to severe asphyxia, premature placental detachment, and prematurity.